REGIONAL ANALYSIS OF EXPORT/IMPORT INFLUENCE OVER PRODUCTIVITY TOWARD REGIONAL GROWTH - , Fadil, Ir. Leksono Probo Subanu, MURP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Indonesiaâs National Development Planning (RPJMN) of 2010-2014 emphasizes the improvement of export/import. It implies that Indonesian Government believes that export/import can boost economic growth. Indonesian Government shares belief with the group of experts that advocates the importance of openness in export/import. Actually, there is another group that considerably has different ideas. This group does not support such aggressive effort to improve export. Theoritically, to achieve and maintain sustainability of economic growth, countries need sustainability of productivity. Export/import is considered as a factor that can support sustainability of productivity. The research tries to reveal the relationship of local openness and productivity in each province. A cross-province panel data analysis is used to mainly examine the relationship between local/provincial openness (export/import rate) and productivity over provinces in Indonesia. The main variable used is local openness of provinces and productivity (solow residual). The model used is developed from Cobb-Douglas production function that is often used to measure growth of a country. The data set used for the analysis consists of data from 33 provinces ranging from 2008 to 2012. The data set is regressed by using OLS regression. By regressing local openness as independent variable with respect to productivity (solow residual) as independent variable, the positive/negative coefficient of local openness of each province can be obtained as the relationship between the variables in each province can be analyzed. The result is also compared with the macro strategy of export/import planning as stated in Indonesiaâs National Development Planning of 2010-2014 (RPJMN II). This research proves that there is positive impact of local openness over productivity growth in most provinces.